RANCANGAN SISTEM KELISTRIKAN DATA CENTER BERSTANDAR TIER 3 PADA PERBANKAN - Anggi Suryanti, Ni Made Vifiana; Suweden, I Nengah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p41, 2023)
A data center is a facility used to place electronic systems and related components for the purposes of placing, storing and processing data. The data center is expected to be able to provide services as optimally as possible even in the event of a disturbance. Data center development must consider long-term development plans in terms of services, hardware and infrastructure. The majority of data centers in Indonesia are still standard tier 2. The majority of data centers with tier 3 standards have qualified specifications for companies that require high availability with good planning of the appropriate electrical system. The results of the research that has been done is that in designing a tier 3 standard data center, it must have full backups in the form of generators and UPS to meet the No Shutdown requirements. The use of estimated power designed in this study is 289433 Watts using a main power source from PLN using two transformer units backed up by four generator units and one UPS unit to back up critical loads.